Biomarkers in patients with Takotsubo cardiomyopathy compared to patients with acute anterior ST-elevation myocardial infarction. (17th February 2020) - Højagergaard, Mathias Alexander; Hassager, Christian; Christensen, Thomas Emil; Bang, Lia Evi; Gøtze, Jens Peter; Ostrowski, Sisse Rye; Holmvang, Lene; Frydland, Martin
Abstract: Background: Takotsubo cardiomyopathy (TTC) is a syndrome of acute non-coronary heart failure with similar symptoms and electrocardiograms to acute anterior ST-elevation myocardial infarction (STEMI). Little is known about the pathophysiology of TTC. We assessed admission plasma concentrations of biomarkers reflecting neuroendocrine response (copeptin, mid-regional-pro-adrenomedullin, pro-atrial-natriuretic-peptide, soluble thrombomodulin (sTM), syndecan-1) and inflammation (suppression-of-tumorigenicity 2 (ST2), high-sensitive C-reactive-protein) in TTC patients and compared to patients with acute anterior STEMI. Materials and methods: Twenty TTC patients were matched with 40 STEMI patients by age, gender and left ventricular ejection fraction. Blood was sampled upon hospital admission immediately before acute coronary angiography. Results: The groups had similar comorbidities. TTC patients had higher plasma concentrations of sTM: 7.94 (5.89;9.61) vs. 6.42 (5.50;7.82)ng/ml, p = 0.04 and ST2 (53 (32;157) vs. 45 (31;55)ng/ml, p = 0.008) and higher heart rate: 101 ( ± 33) vs. 76( ± 14)bpm, p = 0.0001, but lower concentrations of copeptin (10.4 (7.6;39) vs. 92.3 (13;197)pmol/l, p < 0.05) and troponin T (348 (98;759) vs. 1190 (261;4105)ng/l, p = 0.04). Conclusion: TTC patients had higher plasma concentrations of sTM and ST2, higher heart rate and lower copeptin and troponin T concentrations compared to acute anterior STEMI patients. This study contributes to the hypothesis that TTC patients have endothelial cell damage and are hemodynamically more stable than patients with acute anterior STEMI on admission.